Physiological and Cognitive Functions Following a Discrete Session of Competitive Esports Gaming - Sousa, Amber; Ahmad, Sophia L.; Hassan, Tamzid; Yuen, Kyle; Douris, Peter; Zwibel, Hallie; DiFrancisco-Donoghue, Joanne (Frontiers in Psychology, 2020)
Competitive electronic and video games, collectively termed “esports” have become an international industry. The physiological and cognitive health results of esports practice and competition have not been adequately studied. The current study examined physiological and cognitive changes after a session of esports game play for two types of games, First Person Shooter and Multiplayer Online Battle Arena. Increases in systolic blood pressure, increases in speed, and decreases in accuracy and inhibitory processes were found for all esports gamers. For peak heart rate change, First Person Shooter games elicited a larger change than Multiplayer Online Battle Arena games. These results have implications for the management of esports player cognitive and physical health as well as for the optimization of performance in competitive esports tournaments.